HUBUNGAN PENGGUNAAN CAHAYA BUATAN SAAT TIDUR TERHADAP KUALITAS TIDUR PADA MAHASISWA PROGRAM STUDI ILMU KEPERAWATAN UNIVERSITAS RIAU - Nurul " Afika; Darwin " Karim; Febriana " Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Individuals are required to meet basic human needs, one of that is sleep. The young adults often experience sleep disturbances. The aims of this research was to determine the correlation between the artificial light while sleeping with the sleep quality of students of nursing at the University of Riau.  Research design with cross-sectional approach. The research sample was 137 respondents were taken based on inclusion criteria using total sampling technique. The measuring instrument used is the question sheet for variable artificial light, and a questionnaire for variable quality of sleep. The analysis used univariate analysis to determine the frequency distribution and bivariate using chi square test. The results showed 28 (20,4%) respondents had a good sleep quality and 109 (79,6%) respondents had poor sleep quality, and the results also showed from 137 respondents, as many as 106 (77,4%) respondents use direct light while sleeping and 31 (22,5%) respondents use indirect light while sleeping. The statistical results obtained p value (0,001) < (0,05), it can be concluded that there is a significant relationship between the use of aritifical light while sleeping on the quality of sleep. For subsequent researchers are strongly advised to examined about the types of lights that can affect the quality of sleep, especially for PSIK UR student. Keyword: Artifical light, Sleep quality.